2008
DOI: 10.1111/j.1582-4934.2008.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Applications of SELDI‐MS technology in oncology

Abstract: Considerable interest, speculation and controversy have been generated utilising surface-enhanced laser desorption/ionization in conjunction with mass spectrometry (SELDI-MS) for the diagnosis, prognosis and therapeutic monitoring of cancer and offers an attractive approach to cancer biomarker discovery from tissues and biological fluids. This technology utilises a combination of mass spectrometry and chromatography to facilitate protein profiling of complex biological mixtures. Compared to some other more tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 85 publications
(98 reference statements)
0
42
0
Order By: Relevance
“…Various biofluids including plasma, serum, saliva, urine, tears, amniotic fluid, cerebrospinal liquid, bronchoalveolar fluid, and nipple aspirate fluid were analyzed by SELDI-TOF/MS to identify biomarkers for disease diagnosis . A large number of studies have been reported on the applications of SELDI-TOF/MS in protein profiling of biofluid samples for disease, particularly cancers such as breast, prostate, hepatocellular, ovarian, nasopharyngeal, testicular, colon, lung, pancreas, choriocarcinoma, osteoarthritis, remote ischemic preconditioning, and juvenile idiopathic arthritis [284][285][286][287][288][289][290][291][292][293][294]. The results of these studies showed a potential for large-scale disease screening using SELDI-TOF/MS.…”
Section: Surface-enhanced Laser Desorption/ionizationmentioning
confidence: 98%
“…Various biofluids including plasma, serum, saliva, urine, tears, amniotic fluid, cerebrospinal liquid, bronchoalveolar fluid, and nipple aspirate fluid were analyzed by SELDI-TOF/MS to identify biomarkers for disease diagnosis . A large number of studies have been reported on the applications of SELDI-TOF/MS in protein profiling of biofluid samples for disease, particularly cancers such as breast, prostate, hepatocellular, ovarian, nasopharyngeal, testicular, colon, lung, pancreas, choriocarcinoma, osteoarthritis, remote ischemic preconditioning, and juvenile idiopathic arthritis [284][285][286][287][288][289][290][291][292][293][294]. The results of these studies showed a potential for large-scale disease screening using SELDI-TOF/MS.…”
Section: Surface-enhanced Laser Desorption/ionizationmentioning
confidence: 98%
“…Surface-enhanced laser desorption/ionization mass spectrometry (SELDI-MS) is a proteomic analysis (10) that has been demonstrated to be a very suitable approach to evaluate complex variations on protein level in tissue and cells (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The technology utilizes a combination of MS and chips with affinity to specific protein types to facilitate protein profiling of complex biological mixtures. It has higher throughput capability than 2D polyacrylamide gel electrophoresis [3]. Preliminary studies using SELDI-TOF MS assessment of body fluids to detect breast cancer have focused primarily on serum and plasma.…”
mentioning
confidence: 99%